Fabrication-friendly all-optical plasmonically-enhanced integrated phase-change photonic memory device - Song, Junchao; Pady, Joe; Gemo, Emanuele; Farmakidis, Nikolaos; Bhaskaran, Harish; Bente, Ivonne; Pernice, Wolfram; Wright, C. David (Optics express, 2025)
The potential for realizing fast, energy-efficient integrated photonic memory and computing devices developed from the nanoscale light-squeezing and electric-field enhancing capability of plasmonic resonant structures and the intrinsic tuneability of chalcogenide phase-change materials is explored. We concentrate on designs that should be readily manufacturable, comprising a plasmonic dimer-bar nanoantenna deposited on top of a phase-change cell, itself deposited on top of an integrated photonic waveguide. Device optical properties and switching behavior are determined by a combination of finite-element thermo-optic and bespoke phase-change computational models. The results show that suitably designed devices can achieve switching energies in the tens of pico-Joule range and switching speeds in the tens of nanosecond range, a very considerable improvement over conventional designs, and showing a good trade-off between the device performance and fabrication complexity.